(3QSGdI GdJfRjI Edi LeGYI GdehMOjfs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3JhcdJ Ydi ehdGfG GdHGQ GdYdGe HSe Gddg GdQMef GdQMje OYGI YHOg GdEeGe ef YHO YQa ehdGfG ai GdXghQ hGdcJeGf hYHOg s
(3BNQgG (B:s
(3hehdGfG SHMGfg efRg Yf MOhO GdOjf hGdOfjG dGjONd ai GdChgGe hGdNhGWQ SHMGfg hJYGdi YeG jUahf hMOg dGTQjc dg JeJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B18s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdJhMjO hGdedd hGdfMds